KONSEP BANK KELILING SYARIAH DALAM MEMENUHI KEBUTUHAN DI DESA KRANDON KECAMATAN KESESI - Nely HIkmawati (Sahmiyya, 2023)
The purpose of this study is to explain the concept of syariah mobile banking in meeting needs in Krandon village, Kesesi district. This research method was carried out using a qualitative approach and data collection using two sources, namely primary data and secondary data. Primary data obtained by interview while secondary data obtained from literature studies. the Islamic view of the practice of debt Debt is permissible and encouraged by Islam. It is permissible if in practice and implementation it complies with the provisions, procedures and rules of the game applied in Islam. the factors behind the occurrence of debt transactions in Krandon village are due to an urgent need and the process is easy and fast. Or in other words, they feel that they are facilitated in covering their daily needs with this transaction Their level of understanding of fiqh muamalah was minimal, causing the people in Krandon Village to carry out debt transactions that are clearly prohibited in Islam, namely by them owing to mobile banks who clearly took the profits required at the beginning. The Islamic prohibition of usury is stated repeatedly in Q.S. Ar-rum 30/39; Q.S. An-nisa 4/161; Q.S. Ali-Imran 30/130 and Q.S. Al-Baqarah 2/278-279. One type of financing that is most suitable for residents who borrow from mobile banks is the qardul hasan contract, which is a type of loan without interest or profit.